Jawabanmu

Jawaban paling cerdas!
2014-05-31T10:18:07+07:00
f(x) = 3x^ - 2 dan g(x) = 2x/x-3, (fog)(2)
(fog) = f(g(x))
       = f (2x)
            x - 3
       = 3
(2x)^ - 2
             x - 3
       =   3 (4x^)     - 2  
          x^ - 6x + 9
       = 12x^ - 2 (x^ - 6x + 9)
            x^ - 6x + 9
       = 12x^ - 2x^ + 12x - 18
             x^ - 6x + 9
       = 10x^ + 12x - 18
            x^ - 6x + 9
(fog) (2) = 10.4 + 12.2 - 18
                4 - 6.2 + 9
             = 46/1
            = 46
3 4 3
2014-05-31T10:18:10+07:00
G(2) = 2.2 / 2-3 = -4
f(-4) = 3(-4)^2 - 2 = 48 - 2 = 46
jawaban: 46